Performance of mungbean (Vigna radiata) varieties at different row spacings and nitrogen phosphorus fertilizer levels* - TICKOO, J L; CHANDRA, NARESH; GANGAIAH, B; DIKSHIT, H K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during rainy season (kharif)22000 to find out agronomic requirements of mungbean [Vignn radiata (L.) Wilczek]. The varieties and spacings had significant influence on biological yield, grain yield and harvest index of mungbean. ’Pusa Vishalbout yielded ’Pusa 105’ in terms of grain yields. Among the interaction effects, variety x spacing and spacing x N-P,O, have been found significant on grain yield of mungbean.